Pesan Dakwah Dalam Novel “Tentang Kamu” Karya Tereliye - Suci Yohanifah (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2022)
Tere Liye's novel is a novel that tells about the life journey of Sri Ningsih, how he faced a life full of trials and obstacles but still passed with patience and sincerity, This novel is very useful for anyone to live a patient and sincere life. This research aims to find out the message of da'wah challenge patience and sincerity in Tere Liye's novel Tentang Kamu. In this study using a qualitative approach that is by analyzing the text of the messages in the novel and produce a message of da'wah about patience and sincerity. This research is a literature or literature research with a primary source is Tere Liye Novel Tentang kamu and secondary books, articles, internet journals about patience and sinceriry. The result of his research is that there are several messages about patience, namely patience in carrying out obligations to the creator in this novel Sri Ningsih becomes a devoted child to parents by carrying out all the mandates of his father Nugroho even after the death of his father Nusi Maratta his stepmother treated Sri Ningsih badly, the second patient in avoiding herself from the benefits that is when Sri Ningsih was able to avenge him to Nusi Maratta he still chose to forgive and not avenge her,the third patient in the face of the destiny of Allah SWT this message is in the story of Sri Ningsih patiently when his father Nugroho died.Furthermore, the message of da'wah about Ikhlas in releasing the departure of the father of the child and her husband, both sincerely received all sri's property burned in one day and tried to rise again from the slump.